Application of granular and ozone-biological activated carbon treatments for the mitigation of organic chemical peaking events in potable water schemes - George William Kajjumba; Ceonie M.M. Washington; Aarthi Mohan; Zita L.T. Yu; Larry Schimmoller; Jesus Gonzalez; R. Scott Summers; Eric R.V. Dickenson (Water Research X)
Direct potable reuse employing reverse osmosis (RO) and advanced oxidation processes (AOP) is emerging as a solution to combat water scarcity in many communities. However, the intermittent passage of low molecular weight (LMW) volatile organic compounds (VOCs) through RO/AOP presents a public health concern. This study assessed two potential add-on treatment strategies: 1) granular activated carbon (GAC) treatment after RO/AOP and 2) ozonation followed by biological activated carbon (O3/BAC) treatment before RO/AOP. Rapid small-scale column tests (RSSCTs) simulated GAC performance with three intermittent spiking events of individual LMW VOCs—acetone, formaldehyde, methyl tert-butyl ether (MTBE), 1,2-dichloroethane, and 1,2,3-trichloropropane—in RO/AOP product water (50–300 µg/L). A pilot-scale O3/BAC system treating tertiary-filtered wastewater was also evaluated under similar spiking conditions. GAC RSSCTs achieved higher reductions of haloalkanes (>98 %), MTBE (>98 %), and acetone (47 %) compared to O3/BAC. In contrast, formaldehyde was effectively removed by O3/BAC (>98 %) via biotransformation, while GAC had limited efficacy (<30 %). Spiked VOCs temporarily reduced N-nitrosodimethylamine removal in the O3/BAC system, but baseline performance recovered. These preliminary results suggest GAC post-RO can mitigate haloalkane and ether-like VOC peaks, although real-world monitoring and long-term pilot testing are needed. O3/BAC is suited for removing biodegradable compounds like formaldehyde but may require optimization. Additional strategies, such as air stripping, activated sludge pretreatment, and blending, should be further explored to address LMW chemical peaking in potable reuse schemes.